The potential of Geography fieldwork projects to develop action competence in response to social-ecological concerns: a case study of two Grade 10 Geography classes in Northern Namibia - Mwiila, Modestus (Rhodes University, Faculty of Education, Department of Education, 2020)
The study explored the potential of Geography fieldwork projects to develop learners' action competence in response to social-ecological problems in two schools in the Omusati and Oshana Education Regions. The study investigates ways in which learners' activities create an opportunity for them to act for the environment. That is, to investigate ways in which learners can be shaped into environmentally literate citizens who act for the environment. A total of 43 grade 10 learners and two grade 10 Geography teachers participated in this qualitative, interpretive case study. Data was generated through document analysis, focus group interview with learners, semi-structured interviews with educators, and participant observations. Such data were analysed into three phases, first inductively and then abductively using Jensen's (2004) Investigations, Visions, Actions and Change (IVAC) model to produce analytic statements that form the basis of the research findings. The study found that Geography fieldwork projects foster understandings of environmental problems in a local area. Through fieldwork projects, schools initiate indirect environmental actions, however, some environmental problems are too large or complex to be resolved by the actions initiated by learners. Based on these findings, the study identifies Geography fieldwork as an opportunity to create a community of practice in effort to address socioecological concerns. The study further recommends that learners should be allowed to engage with both social investigative actions and technical, scientific investigative actions when doing project work.
Keywords: Geography -- Study and teaching (Secondary) -- Namibia